Potential drug-drug interactions in hospitalized patients with COVID-19. - Danuta Szkutnik-Fiedler; Filip Kwiatkowski; Monika Chomej; Dorota Kołodziej; Michał Michalak; Edmund Grześkowiak; Edyta Szałek (Polskie Towarzystwo Farmaceutyczne, 2023)
Most hospitalized patients with COVID-19 require complex pharmacotherapy due to underlying diseases, and polypharmacy may significantly increase the risk of drug-drug interactions (DDIs) and, in consequence, trigger adverse effects. The aim of this study was to assess the risk of potential DDIs during hospitalization in COVID-19 patients. A retrospective analysis of pharmacotherapy in 75 patients (age, Mean±SD, 63.6±14.9) with a proven diagnosis of SARS-CoV-2 infection was conducted. The analysis included drugs administered to treat comorbidities and the COVID-19 treatment. 524 moderate and 112 major interaction cases were revealed in the analyzed COVID-19 patients, and 84% of the patients were exposed to at least one major DDI. Drugs that caused the most frequently observed DDIs include macrolides, low molecular weight heparins, glucocorticosteroids, quinolones, and antihypertensive drugs. Most COVID-19 patients have comorbidities requiring polypharmacy, which increases the risk of DDIs. Therefore, additional monitoring should be considered due to potential adverse effects, drug conversion, and deprescription.